Pembentukan Karakter Siswa: Studi Integrasi Nilai-Nilai Pendidikan Agama Islam Dalam Proyek Penguatan Profil Pelajar Pancasila dan Budaya Kerja (P5BK) di SMKN 1 Masbagik - Putra, Yusril Mustapa; Supardi, Supardi; Irrubai, Moh. Liwa (Jurnal Ilmiah Profesi Pendidikan, 2023)
This study aims to integrate Islamic Education values into the Strengthening Pancasila Student Profile and Work Culture Project (P5BK) to shape student character at SMKN 1 Masbagik. The research employs a qualitative descriptive method. Data were collected through interviews, observations, and document studies, and then analyzed using Miles and Huberman's interactive model. The results show that the integration of P5BK with Islamic Education values at SMKN 1 Masbagik is implemented through projects with themes of sustainable lifestyle, employability, and local wisdom. The implementation of P5BK involves four stages: planning, execution, evaluation, and supportive factors. The advantages of this integration include flexibility in implementation, synergy with the community and the workforce, and providing real-world experiences to foster student awareness of their environment and surrounding community. The theoretical implication of this research is its contribution to the support and enhancement of P5BK learning as part of the independent learning curriculum, which can improve teacher competence and the quality of education in vocational schools.